2013
DOI: 10.1371/journal.pone.0077038
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Avoidance in Injection Drug Users: A Typology of Possible Protective Practices

Abstract: IntroductionHepatitis C virus (HCV) represents a serious public health concern. People who inject drugs (PWID) are at particular risk and nearly half (45%) of PWID in England may be infected. HCV prevention interventions have only had moderate impact on the prevalence of HCV in this population. Using qualitative methods, we sought to detail the protective practices potentially linked to HCV avoidance among PWID, and explore the motivations for these.MethodsThe study used a life history approach allowing partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Specifically, reviews of harm reduction strategies have shown needle exchange programs to likely be modestly effective in preventing HCV infection , whereas the evidence for opiate substitution treatment [e.g. methadone maintenance treatment (MMT)], behavioral interventions and syringe disinfection is less convincing . Among the reviews of addiction treatments, a recent systematic review and meta‐analysis found that various forms of addiction treatment, including MMT, were not effective in reducing the risk of HCV .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, reviews of harm reduction strategies have shown needle exchange programs to likely be modestly effective in preventing HCV infection , whereas the evidence for opiate substitution treatment [e.g. methadone maintenance treatment (MMT)], behavioral interventions and syringe disinfection is less convincing . Among the reviews of addiction treatments, a recent systematic review and meta‐analysis found that various forms of addiction treatment, including MMT, were not effective in reducing the risk of HCV .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, other authors suggested that in the absence of a needle and syringe, some users might snort or smoke heroin [ 30 ]. However, our results point to injecting as the sole route of administration among drug injectors in Kulob and Khorog.…”
Section: Discussionmentioning
confidence: 99%
“…London-based findings pertaining to the central study aim have been widely reported. We found that social practices not directly or proximally linked to hepatitis C such as social relations of methadone diversion, stigma avoidance, drug use preparedness, and venous care might, nonetheless, have hepatitis C prevention effects (Harris & Rhodes, 2013a, 2013bHarris, Treloar, & Maher, 2012;McGowan, Harris, & Rhodes, 2013). This article is the first to explore how the life history methods employed informed these findings and the everyday ethical dilemmas encountered in this process.…”
Section: The Studymentioning
confidence: 91%
“…and T.R. to develop concept-driven categories and then, with reference to the life-grids, themes with transferable harm reduction utility (see Harris & Rhodes, 2012, 2013a, 2013b; McGowan et al, 2013). Field notes and transcript data pertaining to the methodological process inform analysis presented in this article.…”
Section: The Studymentioning
confidence: 99%